RESPONSE OF SELECTED TREE SEEDLINGS TO ROOT-KNOT NEMATODE (Meloidogyne incognita) - Tanimola, Adebowale Adegboyega; Ezeunara, E. A. (FUDMA JOURNAL OF SCIENCES, 2021)
Root-knot nematodes have been implicated in poor growth and death of trees in the nursery and newly established forest plantations. Cultivating resistant tree species is one of the viable methods in the management of nematode pests once they are identified. A pot experiment laid out in completely randomized design was conducted to screen fifteen selected tree seedlings for resistance to Meloidogyne incognita. Each tree seedling was replicated eight times and was grown on a steam-sterilized soil. The seedlings were inoculated each with 7,000 eggs of Meloidogyne incognita at four weeks after planting. Data were collected on plant height and stem girth at 12 weeks after inoculation. At termination, data were also collected on gall index (GI), final nematode population (Pf) and reproductive factor (RF). Data were analyzed using analysis of variance. Resistance or susceptibility status was assigned with Canto-Saenz host designation scheme. There was variability in the growth of the tree seedlings. Simphonia africana had the highest GI, Pf and RF of 3.3, 54,500 and 22.07, respectively and these values were significantly higher than values from other seedlings. Six tree seedlings;  Simphonia africana, Theobroma cacao, Gmelina arborea, Piptadeniastrum africana, Chrysophyluum albidium and Parkia biglobosa were found to be susceptible to M. incognita, while six (Tetrapleura  tetraptera, Anacardium occidentale, Annonas muricata, Dinium  guinensis and Vitex doniana) were found to be resistant and three (Treculia africana, Mangifera indica  and  Dacryodes edulis) were tolerant. Resistant tree seedlings should be planted in M. incognita-infested plantation and susceptible species should be treated even in
Keywords: Meloidogyne incognita, Nematode population, Reproductive factor, Resistance, Tree seedlings